Design of Flat With Neighborhood Space With Urban Farming Function In Medan - Adela Purba; Nelson Siahaan (Talenta Publisher, 2021)
In Medan, flats do not utilize neighborhood space as an urban farming area. In general, flats have a high density of occupants, inflexible designs, and the relationship between one door to another door is relatively close so that communal space is needed. Communal space is a space that functions as a place for social interaction activities for its residents. This flat design has green open spaces such as neighborhood space that can be used as communal spaces both socially and economically productively (urban farming) because flats require both functions. The design approach process used in this design is primary data collection through a field study process and physical data collection that supports scientific and factual data processing. The design analysis was carried out based on the results of literature review and data collection to identify the character of the design area, problems that arise, limitations and potentials, functional requirements, then conduct a review of the regional development plan. This flat is designed using an Ecological Architecture approach to reduce environmental problems in urban areas. The design creates a flat that considers the needs of communal space, green open space, and recreation areas to meet the needs of users. This design can create facilities for the community and become a tourist attraction.